2014
DOI: 10.1186/s13075-014-0497-x
|View full text |Cite
|
Sign up to set email alerts
|

Synovial T cell hyporesponsiveness to myeloid dendritic cells is reversed by preventing PD-1/PD-L1 interactions

Abstract: IntroductionThe aim of this study was to investigate PD-1/PD-L1 involvement in the hyporesponsiveness of rheumatoid arthritis (RA) synovial fluid (SF) CD4 T cells upon stimulation by thymic stromal lymphopoietin (TSLP)–primed CD1c myeloid dendritic cells (mDCs).MethodsExpression of PD-1 on naïve (Tn), central memory (Tcm) and effector memory (Tem) CD4 T cell subsets was assessed by flow cytometry. PD-L1 expression and its regulation upon TSLP stimulation of mDCs from peripheral blood (PB) and SF of RA patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 31 publications
3
18
0
Order By: Relevance
“…Although the highest tested concentration (100 µM) of both statins showed a cytotoxic effect on mDCs, statin concentrations of 1−10 µM did not affect the mDC survival. We next investigated the effect of statins on mDC maturation by measuring the expression of CD40, CD80, CD83, CD86, HLA‐DR, and programmed death ligand 1, known to be induced by the culture with TSLP or TLR‐ligand stimuli . MFI of these markers remained unchanged in the presence of 1−10 µM of pitavastatin or simvastatin (Fig.…”
Section: Resultssupporting
confidence: 86%
“…Although the highest tested concentration (100 µM) of both statins showed a cytotoxic effect on mDCs, statin concentrations of 1−10 µM did not affect the mDC survival. We next investigated the effect of statins on mDC maturation by measuring the expression of CD40, CD80, CD83, CD86, HLA‐DR, and programmed death ligand 1, known to be induced by the culture with TSLP or TLR‐ligand stimuli . MFI of these markers remained unchanged in the presence of 1−10 µM of pitavastatin or simvastatin (Fig.…”
Section: Resultssupporting
confidence: 86%
“…TSLP priming resulted in PD-L1 upregulation on DCs, which could negatively regulate PD-1-expressing T cells. However, it was shown that the abundance of IL-7 in RA joints plays a critical role in overcoming PD-1-mediated inhibition of T cells, leading to the prevalence of T-activating effects [164,165]. Furthermore, GM-CSF produced by synovial CD4 þ T cells supported the differentiation and activation of infDC, thus promoting a local inflammatory amplification loop [166].…”
Section: Cdc Activationmentioning
confidence: 99%
“…PD-L1 is widely expressed in activated endothelial and epithelial cells, and it is therefore thought to be important for the fine-tuning of lymphocyte activation at the level of synovial tissue [ 20 , 21 ]. Increased numbers of PD-1 + and PD-L1 + cells were found in the synovium of patients with active RA [ 22 – 24 ].…”
Section: Introductionmentioning
confidence: 99%